Inside the criminal courts - Lynch, David R. (Carolina Academic Press, 2016)
The legal education of lawyers and judges -- A day in juvenile court -- Justice delayed -- The criminal defense attorney -- The prosecuting attorney -- The judge -- The witness -- The steps of due process -- The plea bargain -- The trial (Part I) -- The trial (Part II) -- The jury deliberates -- Sentencing -- The appeal -- Problem-solving courts -- Proposed reforms